2012
DOI: 10.1136/bmjopen-2012-001783
|View full text |Cite
|
Sign up to set email alerts
|

Protocol Evaluating the effectiveness of a school-based group programme for parents of children at risk of ADHD: the ‘PArents, Teachers and CHildren WORKing Together (PATCHWORK)’ cluster RCT protocol

Abstract: IntroductionEarly intervention for childhood behavioural problems may help improve health and educational outcomes in affected children and reduce the likelihood of developing additional difficulties. The National Institute for Health and Clinical Excellence guidelines for attention deficit/hyperactivity disorder (ADHD), a common childhood behavioural disorder, recommend a stepped care approach for the identification and management of these problems. Parents of children with high levels of hyperactivity and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Further details are given in the trial protocol (Sayal et al . ). Eligible schools were large, mixed‐sex primary schools across three counties of the East Midlands, UK (Nottinghamshire, Derbyshire and Lincolnshire), incorporating a range of socio‐economic status.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Further details are given in the trial protocol (Sayal et al . ). Eligible schools were large, mixed‐sex primary schools across three counties of the East Midlands, UK (Nottinghamshire, Derbyshire and Lincolnshire), incorporating a range of socio‐economic status.…”
Section: Methodsmentioning
confidence: 97%
“…As described in the trial protocol (Sayal et al . ), the outcome measures were completed 6 months after baseline. These included the short version of Conners' Parent and Teacher Rating Scales – Revised (Conners ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As this period is determinant in terms of development, many intervention programs such as "I Can Problem Solve" and "First Step to Success," aimed at supporting development, are targeted at children aged 3-6 (Baydar et al, 2010). Social and emotional intervention programs assist children exhibiting behavioral problems in fulfilling their educational attainment and healthy development, and also in reducing the possibility of other problematic conditions arising (Sayal et al, 2012). In the context of an interdisciplinary approach, studies have found that social-emotional intervention programs provide significant positive gain, encouraging competence and life skills to the benefit of children's mental health and sound condition (Tennant, Goens, Barlow, Day, & Stewart-Brown, 2007;Weare & Nind, 2011;Wells, Barlow, & Stewart-Brown, 2003).…”
mentioning
confidence: 99%